Preservation of a Dust Crystal as it Falls in an Afterglow Plasma - Chaubey, Neeraj; Goree, J. (Frontiers in Physics, 2022)
In an experiment, the power that sustains a plasma was extinguished, so that microspheres, which had been levitated, fell downward toward a lower electrode. At the beginning of their fall, the microspheres were self-organized with a crystalline structure. This structure was found to be preserved as the microspheres accelerated all the way to the lower electrode. Although microspheres had, in this afterglow plasma, large positive charges of 12,500 e, their interparticle repulsion was unable to significantly alter the crystalline arrangement of the microspheres, as they fell. After their impact on the lower electrode, the microspheres bounced upward, and only then was the crystalline structure lost.